Anotaciones - . Ideas y Valores (Ideas y Valores)
Louis Althusser / Juergen Habermas / Jean - Toussaint Desanti / Paul Ricoeur / Alfred Schmidt / Noël Mouloud / Ramon Garzón / Jorge Aurelio Diaz / Freddy Téllez / Fernando Urbina / Breve bibliografía sobre el tema de la ideología